About the quantitative and qualitative approaches in the current Cuban educational investigation - Torres Fernández, Paul A. (Atenas, 2016)
This article makes an analysis of the use of the quantitative and qualitative approaches in the current Cuban educational investigation, with the revision of more than a thousand thesis and results of investigation of the last two decades. As consequence of that analysis, it was verified that there has been an incoherent transfer of resources proper of one approach into the other and a low level of employment of both with the necessary methodological coherence.